(untitled) (Management and Connections Journal, 2025)
The present study aims to understand the purchase decision journey of LGBT consumers in relation to clothing brands, comparing how each minority in this group behaves in relation to the loyalty cycle proposed by Edelman (2010). This study is important for the business area, since there are few published works that involve the LGBT community, becoming a source of information for future research and incentive for companies looking for new market opportunities aimed at this audience. The research was qualitative and exploratory. Data collection took place through seventeen interviews with self-declared lesbian, gay, bisexual and transsexual people, who completed a Free and Informed Consent Form. The instrument for data collection was a semi-structured script. The Google Meet software was used to record the interviews, which were subsequently transcribed. NVivo software was used for thematic and comparative content analysis, generating frames and word clouds. The survey data shows that LGBT consumers follow the Loyalty Cycle (Edelman, 2010) in very close ways, except for some issues regarding product research. And yet, the boycott is a stage of consumer behavior that appears repeatedly in the respondents’ responses, a stage that is not foreseen by the model proposed by Edelman (2010). Therefore, the data shows that LGBT people look for price, quality and comfort when considering a clothing item. Still, social and political factors can lead them to boycott the brands.